PENINGKATAN KAPASITAS MASYARAKAT PESISIR TERHADAP DAMPAK PERUBAHAN IKLIM MELALUI MODEL ‘KAMPUNG IKLIM’ DI DESA BAJO INDAH - Rudi Balaka; Edward Ngii; Adris Ade Putra; Agustan Agustan; Laode M. Golok Jaya; Sitti Nurjannah Ahmad; Tahir Azikin; Ahmad Syarif Sukri; Triantini. S. Putri; Fitriah.S Fitriah.S (Vokasi Universitas Halu Oleo, 2023)
The most obvious phenomenon of the impact of climate change in the coastal area of Bajo Indah village is seen in sea level rise, so that during high tide, sea water enters through the drainage towards the lowlands. Apart from that, another phenomenon is an increase in air temperature, strong winds, high waves and extreme rainfall. In addition, an increase in air temperature causes a decrease in the quantity of clean water, which results in a clean water crisis experienced by the coastal communities of Bajo Indah village. The dominant processes of coastal abrasion and erosion occur along the coast. This coastal area is an area that has a high vulnerability to climate change. One result is the concentration of settlements that are close to the coastline. The purpose of this service is for the community to gain knowledge about the phenomenon of climate change that is occurring so that the community knows and is able to make the necessary adaptations and mitigations to minimize the negative impacts of climate change.